Auditory Screening in Newborns after Maternal SARS-CoV-2 Infection: An Overview - Virginia Fancello; Giuseppe Fancello; Elisabetta Genovese; Stefano Pelucchi; Silvia Palma; Chiara Bianchini; Andrea Ciorba (MDPI AG, 2023)
Background and aim: Several viruses have previously been reported to be responsible for congenital hearing loss; therefore, since the beginning of the SARS-CoV-2 infection pandemic, various reports have investigated a possible link. The aim of this review is to assess the possible link between maternal COVID-19 infection and congenital hearing loss. Methods: This systematic review was performed using PRISMA criteria, searching Medline and Embase databases from March 2020 to February 2023. A total of 924 candidate papers were identified; however, considering the specific selection criteria, only nine were selected for additional analysis. Results: The overall number of children born from mothers infected with COVID-19 during pregnancy identified through this review was 1687. The confirmed cases of hearing loss were 0.7% (12/1688); a description of its nature (sensorineural vs. conductive) is missing in the selected studies, and the follow-up period is variable across the analyzed papers. Surprisingly, a large proportion of false positives were recorded at the first stage of screening, which resulted normal at the re-test. Conclusions: Currently, a correlation between congenital hearing loss and SARS-CoV-2 infection cannot be definitively established. Further studies are desirable to provide additional evidence on this topic.